Postdischarge growth assessment in very low birth weight infants - Joon-Sik Park; Jungho Han; Jeong Eun Shin; Soon Min Lee; Ho Seon Eun; Min-Soo Park; Kook-In Park; Ran Namgung (Korean Pediatric Society, 2017)
PurposeThe goal of nutritional support for very-low-birth-weight (VLBW) infants from birth to term is to match the in utero growth rates; however, this is rarely achieved.MethodsWe evaluated postdischarge growth patterns and growth failure in 81 Korean VLBW infants through a retrospective study. Weight and height were measured and calculated based on age percentile distribution every 3 months until age 24 months. Growth failure was defined as weight and height below the 10th percentile at 24 months. For the subgroup analysis, small-for-gestational age (SGA) and extremely low birth weight (ELBW) infants were evaluated. The growth patterns based on the Korean, World Health Organization (WHO), or Centers for Disease Control and Prevention (CDC) standard were serially compared over time.ResultsAt postconception age (PCA) 40 weeks, 47 (58%) and 45 infants (55%) showed growth failure in terms of weight and height, respectively. At PCA 24 months, 20 infants (24%) showed growth failure for weight and 14 (18%) for height. Growth failure rates were higher for the SGA infants than for the appropriate-weight-for-gestational age infants at PCA 24 months (P=0.045 for weight and P=0.038 for height). Growth failure rates were higher for the ELBW infants than for the non-ELBW infants at PCA 24 months (P<0.001 for weight and P=0.003 for height). Significant differences were found among the WHO, CDC, and Korean standards (P<0.001).ConclusionAdvancements in neonatal care have improved the catch-up growth of VLBW infants, but this is insufficient. Careful observation and aggressive interventions, especially in SGA and ELBW infants, are needed.